THE REALIZED AND EXPECTED EARLY CHILDHOOD INTERVENTION PRACTICES IN LITHUANIA - Alisauskiene, Stefanija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Inclusive early childhood practices are at the forefront of the research and practice efforts in many European countries. Inclusion in early childhood programs can set a trajectory for inclusion across the life course, making it critical that we include individuals with special educational needs in all facets of society from birth. In many European countries, including Lithuania, children with special educational needs and their families continue  facing significant barriers to accessing inclusive high-quality early childhood practices and too many pre-school children with special educational needs and disabilities continue  receiving special education services in separate settings, as opposed to the least restrictive environment. The aim of the research was to assess the realized and expected early childhood intervention practices while educating children with diverse needs in inclusive pre-school settings. The study was based on a survey using the instruments of Recommended Practices in Early Intervention/Early Childhood Special Education. The instrument includes the following topic areas: leadership, assessment, environment, family, instruction, interaction, collaboration, and transition.